An assessment of sales opportunities for a beef feed operation - Taube, Ethan (Kansas State University, 2021)
Animal protein is a critical part of world food supply and food security. The primary sources of animal protein are largely produced in the central United States or Midwest. Midwest Cooperative is a farmer-owned cooperative located in Ames, Iowa. Midwest operates as a grain, agronomy, processing, feed and ecological sustainability organization serving over 7,000 members. The feed business operates as a producer of finished feeds and a distributor of packaged feedstuffs for swine, beef, poultry, mutton and eggs. This thesis is an analysis of the beef feed segment of the business in Jefferson, Iowa. This facility includes milling, mixing, warehousing and repackaging operations. The beef feed business has been identified as a potential opportunity for growth business for the cooperative. The objective of the project is to identify the current market share position of Midwest in the beef feed market. An evaluation was made of the current business performance of the operation. The current market information and the current production data opportunities for the business in the future are identified. The evaluation of the operations indicates that while having a 13 percent share of the local beef feed market, it is failing in achieving profitability. This net loss is driven by high total costs of production. The operation has the capacity to increase its production without any additional investment but the increase in production to maximum levels will leave still 56 percent excess capacity and a net loss to operations. Reimagining the current structure could achieve the desired business enhancement.
Keywords: Beef feed; Cooperative